A pregnancy lifestyle intervention to prevent gestational diabetes risk factors in overweight Hispanic women: a feasibility randomized controlled trial. Issue 1 (29th October 2014) - Hawkins, M.; Hosker, M.; Marcus, B. H.; Rosal, M. C.; Braun, B.; Stanek, E. J.; Markenson, G.; Chasan‐Taber, L.
Abstract Aims To pilot the feasibility of a prenatal lifestyle intervention to modify physical activity and diet among pregnant overweight and obese Hispanic women, with the aim of reducing risk factors for gestational diabetes mellitus. Methods Women were randomized either to a lifestyle intervention (n = 33, 48.5%), consisting of a culturally and linguistically modified, motivationally targeted, individually tailored 6‐month prenatal programme, or to standard care (n = 35, 51.5%). Bilingual and bicultural health educators encouraged women to achieve guidelines for physical activity, decrease saturated fat and increase dietary fibre. Outcomes included gestational weight gain, infant birth weight and biomarkers associated with insulin resistance. Results Patient retention up to delivery was 97% in both study groups. The lifestyle intervention attenuated the pregnancy‐associated decline in moderate‐intensity physical activity, but differences between groups were not significant (mean ± se −23.4 ± 16.6 vs −27.0 ± 16.2 metabolic equivalent of task h/week; P = 0.88). Vigorous‐intensity activity increased during the course of pregnancy in the lifestyle intervention group (mean ± se 1.6 ± 0.8 metabolic equivalent of task h/week) and declined in the standard care group (−0.8 ± 0.8 metabolic equivalent of task h/week; P = 0.04). The lifestyle intervention group also had slightly lower gestational weight gain and infant birth weights compared with the standard care group; however, these differences were not statistically significant. There were no statistically significant differences in biomarkers of insulin resistance between groups. Conclusions Findings suggest that a motivationally matched lifestyle intervention is feasible and may help attenuate pregnancy‐related decreases in vigorous physical activity in a population of overweight and obese Hispanic women. The intervention protocol can readily be translated into clinical practice in underserved and minority populations.